Sarcoidosis in an adult with cystic fibrosis. Issue 10 (October 1989) - Rettinger, S D; Trulock, E P; Mackay, B; Auerbach, H S
Abstract : Sarcoidosis in an adult patient with cystic fibrosis lung disease was diagnosed on the basis of pulmonary function and radiographic data. It should be considered in the differential diagnosis of new diffuse interstitial infiltrates or hilar adenopathy in a patient with cystic fibrosis; biopsy of lung, lymph node, or skin lesions and interleukin-2 receptor levels may help to obtain a diagnosis.